Contribution to the automated designing of positioning of workpieces in the automatic fixtures designing system (Journal of Production Engineering, 1990)
In the scope of developed automated jigs and fixtures designing system one of the modul is the automated designing of positioning of workpieces model. In the first part of this article, it was presented a general model of automated designing of jigs and fixtures and the fundamental base for realization of this model: classification system (specially the block related to the positioning of workpieces) and schemes of placing for realization of corresponding positioning. In the second part of this work there were presented developed algorithms for automated determination of positioning methods and the choice of relevant elements for realization of adequate schemes of positioning. The designing system is generally based on the principle of interaction designer-computer
Keywords: design; fixtures; modul